Sequential and ordered assembly of a large DNA repair complex on undamaged chromatin - Ziani, Salim (The Rockefeller University Press, 2014)
In nucleotide excision repair (NER), damage recognition by XPC-hHR23b is described as a critical step in the formation of the preincision complex (PInC) further composed of TFIIH, XPA, RPA, XPG, and ERCC1-XPF. To obtain new molecular insights into the assembly of the PInC, we analyzed its formation independently of DNA damage by using the lactose operator/repressor reporter system. We observed a sequential and ordered self-assembly of the PInC operating upon immobilization of individual NER factors on undamaged chromatin and mimicking that functioning on a bona fide NER substrate. We also revealed that the recruitment of the TFIIH subunit TTDA, involved in trichothiodystrophy group A disorder (TTD-A), was key in the completion of the PInC. TTDA recruits XPA through its first 15 amino acids, depleted in some TTD-A patients. More generally, these results show that proteins forming large nuclear complexes can be recruited sequentially on chromatin in the absence of their natural DNA target and with no reciprocity in their recruitment.